(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the involvement of the Khiva Jadids in educational activities and how the Jadid intellectuals who came to teach in the New Method schools demonstrated dedication in spreading the ideas of Ismailbek Gasprinskiy, the father of the Jadid movement, among the people of Khorezm.